False Positive Findings of [18F]PSMA-1007 PET/CT in Patients After Radical Prostatectomy with Undetectable Serum PSA Levels - Orevi, Marina; Ben-Haim, Simona; Abourbeh, Galith; Chicheportiche, Alexandre; Mishani, Eyal; Yutkin, Vladimir; Gofrit, Ofer N. (Frontiers in Surgery, 2022)
Background PET-CT using prostate-specific membrane antigen (PSMA)-targeting radiopharmaceuticals labeled with 68Ga or 18F has emerged as the most sensitive staging tool in prostate cancer (PC). Nonetheless, the occurrence of false positive (FP) findings presents a major concern of this approach. In this prospective study, we investigated the frequency and pattern of false-positive findings of [18F]PSMA-1007 PET/CT in patients after radical prostatectomy with undetectable serum PSA levels. Any discrete non-physiological accumulation of [18F]PSMA-1007 in this population is by definition FP. Methods Seventeen men after radical prostatectomy, whose serum PSA levels were <0.05 ng/mL at 2–24 months after surgery were prospectively recruited. PET/CT was acquired at both 1 and 2 h after injection of [18F]PSMA-1007. Findings Three studies (18%) were interpreted as completely normal. Thirty-five foci of “non-physiological” uptake were observed in the remaining 14 (82%) patients, including a single skeletal focus in four patients, multiple skeletal foci in five patients and soft tissue uptake in eight, including in a desmoid tumor and in pelvic lymphocele. The SUVmax of all lesions was in the range of 1–7, except for the desmoid tumor which measured 12.7. All foci were visible in both the 1- and the 2 h studies, presenting a minor (<10%), statistically insignificant increase of SUVmax during this time-interval. Interpretation FP [18F]PSMA-1007-avid foci are found in about 80% of patients with undetectable serum PSA levels. Thus, focal uptake of [18F]PSMA-1007 outside its physiological distribution is not a categorical sign of metastasis and can arise from non-specific uptake of the ligand. The interpretation of [18F]PSMA-1007 PET/CT studies should always consider the clinical context, and lesions with SUVmax < 7 are suspicious for FP.